2021
DOI: 10.1109/access.2021.3050186
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Hemostatic Ultrasonic Scalpel Based on the Longitudinal-Torsional Vibration Mode

Abstract: This paper proposes an ultrasonic scalpel based on the longitudinal-torsional vibration mode to enhance the hemostatic ability. The concentrator of the proposed ultrasonic scalpel has been specially designed with spiral grooves to realize this vibration mode. The change of the working mode has enlarged the vertical motion component of the distal blade to efficiently radiant energy into the dissected tissues, supporting that the blood vessel can receive sufficient energy to be sealed. The electromechanical equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Based on Eq. ( 12) to (15), the values of mechanical impedances can be calculated as a function of excitation frequency, geometric dimensions, and material properties [8,18].…”
Section: Electromechanical Equivalent Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Eq. ( 12) to (15), the values of mechanical impedances can be calculated as a function of excitation frequency, geometric dimensions, and material properties [8,18].…”
Section: Electromechanical Equivalent Circuitmentioning
confidence: 99%
“…Finally, the results have been validated using an impedance analyzer and a laser interferometer (to obtain the displacement amplitude). Li et al [18] designed an ultrasonic surgical scalpel with a longitudinal-torsional combined mode. The electromechanical equivalent circuit method was used to design and achieve the desired resonance frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-assisted machining can reduce the cutting force and prolong tool life, achieving efficient machining of difficult-to-process materials in the aerospace field [7][8][9][10]. Ultrasonic scalpels can achieve the minimally invasive cutting of body tissues, reduce bleeding, and ensure rapid wound healing [11][12][13]. An ultrasonic osteotomy knife can achieve minimally invasive resection of bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the developed wireless ultrasonic scalpel can reduce the power consumption by 12.3 %. Guo [9] designed a hemostatic enhanced ultrasonic scalpel by adding a spiral groove at the end of the ultrasonic guide, but the ultrasonic scalpel produces more heat as the ultrasonic amplitude increases.…”
Section: Introductionmentioning
confidence: 99%